Project-Based Learning (PBL) Model in Improving Critical Thinking of Elementary School Students in Indonesian Language Learning - Hanna Silviana Gunawan; Elma Citra Maylia; Aghista Putri Amelia; Non Dwishiera Cahya Anasta (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Critical thinking skills are one of the skills needed in the 21st century, so learning is required to support the improvement of these skills. The problem-based learning model is one alternative that can be used. This article aims to analyze the results of research related to the PBL Model in improving critical thinking skills of Elementary School students in Indonesian Language Subjects. This study uses the Literature Review and Bibliography Review method. The results of the analysis of this article explain the aspects of critical thinking skills that can be improved through the application of the PBL model in Indonesian language learning, the process of implementing the PBL model in Indonesian language learning, the challenges faced by teachers in implementing the PBL model in Indonesian language learning, improving students' critical thinking skills in Indonesian language learning using the PBL model, and research trends on the PBL model related to the title. Based on this study, the problem-based learning model can be an alternative learning model that can improve critical thinking skills in Indonesian Language learning in elementary schools.